Tea catechins-cross-linked methylcellulose active films for inhibition of light irradiation and lipid peroxidation induced β-carotene degradation. (February 2015) - Yu, Shu-Huei; Tsai, Min-Lang; Lin, Bo-Xian; Lin, Cheng-Wei; Mi, Fwu-Long
Abstract: Methylcellulose is a water soluble cellulose with excellent film-forming properties. However, the utility of methylcellulose in food packaging is limited because it disintegrates readily upon contact with moisture. In this study, an active methylcellulose film was developed using a dry/wet casting method. Tea catechins could permeate into methylcellulose films and physically cross-linked methylcellulose via formation of specific hydrophobic interactions and hydrogen bonds. Cross-linking converted the readily water-soluble methylcellulose film into insoluble methylcellulose–tea catechins (TC–MC) films with high tea catechins-binding capabilities (231.6–391.2 gallic acid equivalent mg/g). The chemical structures and compositions of the complex films were characterized by Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM/EDX). Cross-linking of methylcellulose with tea catechins reduced the water vapor permeability (WVP), swelling ratio and solubility of the films but increased their tensile strengths. The tea catechins binding to MC–TC films provided the films with superior light and water vapor barrier properties. The active films could release unbound tea catechins to scavenge free radicals and inhibit bacterial growth. Degradations of β-carotene caused by ultraviolet-visible light and lipid peroxidation were effectively inhibited by the active films. Graphical abstract: Highlights: Tea catechins (TC)-cross-linked methylcellulose film with high TC-binding capability. Decreasing water vapor permeability, swelling ratio and solubility. Increasing tensile strength and light barrier property. Release tea catechins to scavenge free radicals and inhibit bacterial growth. Inhibit UV-Vis light irradiation and lipid peroxidation induced β-carotene degradation.